Assessing CO2 storage mechanisms in marine shallow sediments to mitigate leakage risks from sub-seabed carbon storage: a numerical simulation study - Hu, Gang; Yi, Xiangyi; Tian, Xuanhua; Wang, Rui; Li, Pengchun; Peng, Linxiong; Liang, Xi (Frontiers in Marine Science, 2025)
The geological storage of CO2 in offshore saline aquifers has been implemented at various sites worldwide. While subsea sediments can serve as a critical barrier against potential leakage from deep storage formations, the mechanisms and storage capacity for CO2 trapping within these sediments remain inadequately understood. This study developed a two-dimensional conceptual model of shallow sediments based on the Enping15–1 Carbon Capture and Storage (CCS) project site in the South China Sea. Furthermore, the CO2-water-rock reaction and storage mechanism were simulated using CMG-GEM, and the process of CO2 leakage into the sediments was investigated. The results indicate that CO2 leakage into the shallow seabed sediments is primarily sequestered through dissolution in pore water, accounting for 70% of the total sequestration, while residual and mineral trapping contribute 10–20%. The dissolution of CO2 leads to pore water acidification, which triggers the dissolution of anorthite and K-feldspar under the prevailing initial geochemical conditions. Dynamic reaction behavior is mainly observed at the leading edge of the acidified plume. However, if the leakage rate exceeds a critical threshold, the advancing acidified plume front causes partial dissolution of previously precipitated carbonate minerals. The critical leakage rate is determined to be 0.2 m³/day for single-point leakage and 0.3 m³/day for multi-point leakage. Notably, multi-point, low-velocity leakage enhances secondary storage within the sediment, thereby reducing the risk of CO2 release into the overlying seawater.